Supramolecular analytical chemistry: Spectrofluorimetric determination of 6-hydroxymelatonin with hydroxypropyl-β-cyclodextrin - Bracamonte, Angel Guillermo (2011)
The effect of the addition of native (α, β and γ) and derivative (methyl-β and hydroxypropyl-β) cyclodextrins (CD) on the fluorescence of 6-hydroxymelatonin (6HM) in water solutions was studied. The fluorescence of the substrate in the presence of hydroxypropyl-β-CD (HPCD) showed the maximum enhancement and the association constant (KA, mol-1 L) was determined (60±2) and interpreted. The fluorescence quantum yield ratio between the complex and free substrate (φ6HMCD/φ6HM) = 6.0±0.2 provides analytical advantages. On the basis of this supramolecular interaction, an alternative and sensitive spectrofluorimetric method for the determination of 6HM was developed with a detection limit of 0.71 ng mL-1. The validation of the method was performed in urine samples with very good recoveries 95-109 %.